Some Aspects of Employment of Young Women from Julian Slovenia in Households of ItalianTowns: A Silent, Bitter-sweet, Never Entirely Spoken out and Heard Story - Mlekuž, Jernej (Two Homelands, 2004)
The contribution deals with poorly researched but massive phenomena of emigrating and employing of young women from Julian Slovenia in households of Italian towns (mainly in the period after World War II). Emigration of women because of work, employment in the household sector was mostly understood as a “push” factor resulting from poverty at home. Women that emigrated and accepted such work have mostly been presented as victims. Suchlike a view in a larger number of cases denoted and still does, as the contribution shows with a presentation of some newspapers articles, the emigrating and employing of women from Julian Slovenia in households of Italian towns. A detailed reading of personal evidences of onetime “dikle” (servant girls) confirms the “weight” of such a view, and on the other hand reveals the phenomena in a much more complex, variegated image. Young women who were “forced to go”, as speaks this dominant narration, “for a better bread” to Italian towns, not necessarily considered themselves victims. Some, as personal evidences reveal, sought “adventure”, at least partly financial independence, they wished to rid (at least to some degree) of the ties of patriarchal society, swap the hard peasant work with a more attractive work in households, or merely make a change in their lives. Not to neglect is the “attractiveness” of the city, which not only was offering the “unreachable and fanciful splendour” but as well opening new life perspectives. “To be a servant girl” in most cases meant just the initial step in the social and/or professional mobility of young women. In a complex understanding of migrations, it is necessary to take into consideration the influences of wider social structures as the intentions, decisions of individuals, or as sociologists would say with a swift stroke, “the structure and functioning”. In addition, if we limit to just one, we can succeed at the utmost to catch only part of a much more interesting, multi-significant and complex story. The contribution also stresses that personal evidence, upon which a lot of dust sat in (approximately) fifty years, should be read most attentively, cautiously and with a certain distance. It is not only about the “consequences” of time remoteness of the phenomena. Namely, it is extremely difficult to view unburdened or “neutral” upon the phenomena of emigration and employment of young women in households as it hardly ever unconcernedly refers to discrimination and exclusion that race, ethnicity, class, gender, religion, education etc. bring.